2017
DOI: 10.1002/ptr.5954
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of Salvianolic acid A on ischaemia‐reperfusion acute kidney injury in rats through protecting against peritubular capillary endothelium damages

Abstract: Renal ischaemia‐reperfusion (I/R) injury is the most common cause of acute kidney injury (AKI). Peritubular capillary (PTC) endothelium damages are an important pathogenesis during I/R AKI. Salvianolic acid A (SAA) possesses various pharmacological activities. The study investigated whether SAA ameliorated I/R AKI through protecting against PTC endothelium damages. Male Sprague–Dawley rats were divided into 6 groups: control, sham, I/R, and I/R plus SAA (2.5, 5, 10 mg/kg) groups. Rats were subjected to bilater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…It has strong antioxidant [24], antibacterial [25], anti-inflammatory, and neuroprotective effects, eventually improving motor and cognitive behavior [26]. Additionally, dihydromyricetin is used to treat osteoporosis, asthma and kidney injury [27,28]. Being a flavonoid that has a role in plant coloration, dihydromyricetin is found to be a substrate for leucodelphinidin production, the latter being the precursor of blue-hued delphinidin [29].…”
Section: Introductionmentioning
confidence: 99%
“…It has strong antioxidant [24], antibacterial [25], anti-inflammatory, and neuroprotective effects, eventually improving motor and cognitive behavior [26]. Additionally, dihydromyricetin is used to treat osteoporosis, asthma and kidney injury [27,28]. Being a flavonoid that has a role in plant coloration, dihydromyricetin is found to be a substrate for leucodelphinidin production, the latter being the precursor of blue-hued delphinidin [29].…”
Section: Introductionmentioning
confidence: 99%
“…Protein levels in MM cells were detected by western blot method, which was performed as previously described (27). MM cells were harvested, washed and lysed with assistance of RIPA Lysis Buffer.…”
Section: Western Blotmentioning
confidence: 99%
“…Studies have shown that DSS could greatly improve blood rheology, lower lipid levels, inhibit lipid peroxidation, and have antitumour and other pharmacological activities [ 13 ]. SAA has protective effects on acute kidney injury induced by ischemia-reperfusion injury [ 14 ] and can greatly attenuate monocrotaline-induced hypertrophic damage of the myocardium, parenchymal injury, and collagen deposition in the lungs [ 15 ]. RA reportedly has a therapeutic effect on type 2 diabetes and hyperlipidaemia [ 16 ].…”
Section: Discussionmentioning
confidence: 99%